2019
DOI: 10.1002/ece3.5221
|View full text |Cite
|
Sign up to set email alerts
|

Postrelease monitoring habitat selection by reintroduced burchell's zebra and blue wildebeest in southern Mozambique

Abstract: Aim In Africa, reintroduction of wild animal species to conservation areas is a common practice, for the recovery or restoration of populations. Effective monitoring of reintroduced species requires understanding of basic ecological requirements such as habitat selection of these species in the new environment. Therefore, the present study investigated the habitat selection of zebra and wildebeest following their reintroduction into Maputo Special Reserve, south Mozambique, and we use binary logistic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Our data indicated that the probability of snake detections was positively correlated with a relatively short distance to water, which was consistent with other studies in that the proximity to water is important for snakes (Brito, 2003;Halstead, Wylie & Casazza, 2010;Sprague & Bateman, 2018). In addition, by employing camera traps we observed that small mammals were more abundant in habitats that were relatively close to water (B Zhang, X Ding & D Yang, personal observations, 2018-2019. Such habitats might provide improved foraging opportunities to Mangshan pit viper.…”
Section: Discussionsupporting
confidence: 90%
“…Our data indicated that the probability of snake detections was positively correlated with a relatively short distance to water, which was consistent with other studies in that the proximity to water is important for snakes (Brito, 2003;Halstead, Wylie & Casazza, 2010;Sprague & Bateman, 2018). In addition, by employing camera traps we observed that small mammals were more abundant in habitats that were relatively close to water (B Zhang, X Ding & D Yang, personal observations, 2018-2019. Such habitats might provide improved foraging opportunities to Mangshan pit viper.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, by employing camera traps we observed that small mammals were more abundant in habitats that were relatively close to water (B. Zhang, X. Ding & D. Yang, 2018-2019. Such habitats might provide improved foraging opportunities to Mangshan pit viper.…”
Section: Discussionmentioning
confidence: 99%
“…Effective conservation and management of species depends on an understanding of habitat requirements, particularly if these aspects change seasonally. This is especially the case for species susceptible to habitat loss or fragmentation (Willems & Hill, 2009;Ali et al, 2017;Mandlate, Cuamba & Rodrigues, 2019). However, information related to habitat requirements is often scarce when a species has low population densities, narrow and remote habitat, receives little low public attention, and when venomous animals can endanger investigators (Rechetelo et al, 2016;Sutton et al, 2017;Leite et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Post-release monitoring is a very useful tool to evaluate animals' fitness and further strengthen wildlife management practices (Myers and Young 2018;Mandlate et al 2019;Prosekov et al 2020). The effective monitoring of an endangered population, and associated conservation planning, requires detailed information relating to behavioral and demographic information (Bhattarai and Kindlmann 2018).…”
Section: Post-release Monitoringmentioning
confidence: 99%